Predicting serotonin toxicity in serotonin reuptake inhibitor overdose. (2nd January 2023) - Cooper, Joyce; Duffull, Stephen B.; Isbister, Geoffrey K.
Abstract: Aims: We aimed to investigate the frequency of serotonin toxicity following overdose of antidepressants that inhibit serotonin reuptake and the factors that influence the probability of serotonin toxicity occurring. Methods: This was a retrospective cohort study of overdoses that included selective serotonin reuptake inhibitors (SSRIs) (70%) and serotonin norepinephrine reuptake inhibitors (SNRIs) (30%) admitted to a tertiary toxicology unit over 23 years. A multivariate mixed effects logistic regression model using NONMEM (7.2.0) was used to determine factors that influenced the probability of serotonin toxicity occurring. Results: There were 1978 overdoses in 1520 patients; median age 33 y (range: 13–86 years) and 64% female. Median defined daily dose equivalent (DDD) was 15 (1–420). Co-ingestants were taken in 1678/1978 (85%) overdoses: 11 co-ingested the monoamine oxidase-A inhibitor (MAOI) moclobemide, 99 (5%) co-ingested olanzapine, 58 (3%) co-ingested risperidone and 417 co-ingested a benzodiazepine (21%). Serotonin toxicity occurred in 269 overdoses (13.6%). The probability of serotonin toxicity increased slightly per 10 DDD units dose [OR, 1.01; 95% confidence intervals (CIs): 0.93–1.10], increased for an SNRI vs . an SSRI [OR, 1.07; 95% CI: 0.99–1.15], and markedly increased with co-ingestion of moclobemide [OR, 33.12; 95% CI: 7.5–147]. The probability decreased per 10 y age [OR, 0.84; 95% CI: 0.74–0.95], and with co-ingestion of the serotonin 2 A receptor (5-HT2A ) antagonists olanzapine [OR, 0.40; 95% CI: 0.17–0.94] or risperidone [OR, 0.13; 95% CI: 0.02–0.99]. The probability of serotonin toxicity was 12.5% at 1 DDD (therapeutic), 12.7% at 15 DDDs and 19% at 420 DDDs. In overdoses of the median dose of 15 DDDs, co-ingestion of moclobemide increased the probability to 83%, and co-ingestion of olanzapine or risperidone decreased it to 5.5% and 1.8%, respectively. Conclusions: Serotonin toxicity is common following SSRI/SNRI overdose. Although dose increases probability, this was only a small effect. Co-ingestion with olanzapine or risperidone reduced the risk 2–6-fold, and moclobemide increased the risk 5-fold.